How to make enemies and influence people: a Social Influence Model of Violent Extremism (SIM-VE). Issue 2 (4th May 2019) - Smith, Debra; Talbot, Steven
ABSTRACT: This paper proposes a Social Influence Model of Violent Extremism (SIM-VE). In the context of increasing concern regarding the role of the internet in engaging people in violent extremist groups, particular attention is paid to the nexus between offline and online environments. The article addresses some of the barriers to developing predictive modelling to identify who will undertake an act of violent extremism and discusses how the SIM-VE model provides a conceptual framework to inform the development of online data gathering and information sorting processes that are relevant to enhancing structured professional judgement of risk. Strengths and limitations of the model are also discussed.